Inhibition of formyl peptide receptor 1 activity suppresses tumorigenicity in vivo and attenuates the invasion and migration of lung adenocarcinoma cells under hypoxic conditions in vitro - Huang, Bo (Ann Transl Med, 2020)
BACKGROUND: Tumor hypoxia has been widely reported to promote metastasis. However, the molecular mechanisms underlying metastasis-associated hypoxia remain unclear. Formyl peptide receptor 1 (FPR1) has been reported to be highly expressed under hypoxic conditions. This study aimed to explore the role of FPR1 in tumor cells under hypoxic conditions. METHODS: The expressions of FPR1 and hypoxia-inducible factor 1α (HIF-1α) in A549 cells under hypoxic conditions were detected using western blot. The expression of FPR1 in A549 cells under hypoxic conditions was suppressed using the FPR1 antagonist Boc2. Wound-healing and Transwell assays were performed to investigate the migration and invasion of cells. Furthermore, the tumorigenicity of A549 cells was evaluated by constructing a hypoxic mouse model of lung adenocarcinoma. The expression levels of HIF-1α and FPR1 in tumors were measured by real-time polymerase chain reaction (PCR) and western blot. RESULTS: The expression levels of FPR1 and HIF-1α increased in a time-dependent manner after exposure to hypoxic conditions. Wound-healing and Transwell assays showed that hypoxia promoted the migration and invasion abilities of A549 cells, whereas downregulation of FPR1 blocked the effects of hypoxia on A549 cells. Our in vivo results demonstrated that the tumor volumes and weights of mice exposed to hypoxic conditions were significantly higher than those of untreated mice. Furthermore, the downregulation of FPR1 blocked the effects of hypoxia in the mice. Meanwhile, the expressions of HIF-1α and FPR1 at the protein and mRNA levels were increased after hypoxic exposure, whereas FPR1 antagonist Boc2 suppressed the effect of hypoxia on the expression of FPR1. CONCLUSIONS: Our results suggest that FPR1 could be a therapeutic target for suppressing the invasion and tumorigenicity of lung adenocarcinoma cells.